The Most Common Vitamin D Receptor Polymorphisms (ApaI,FokI, TaqI, BsmI, and BglI) in Children with Dental Caries: A Systematic Review and Meta-Analysis - Masoud Sadeghi; Amin Golshah; Mostafa Godiny; Roohollah Sharifi; Atefeh Khavid; Nafiseh Nikkerdar; Santosh Kumar Tadakamadla (MDPI AG, 2021)
Vitamin D participates in the calcification of enamel and dentin and the appropriate immune responses to oral microbial infections. We aimed to assess the association between the most common vitamin D receptor (VDR) polymorphisms (ApaI,FokI, TaqI, BsmI, and BglI) and the risk of dental caries in children. Methods: PubMed/MEDLINE, Cochrane Library, Web of Science, and Scopus databases were comprehensively searched until 19 January 2021. Meta-analysis with odds ratios as the effect estimate along with 95% confidence intervals and subgroup analysis were conducted using Review Manager 5.3 software. Publication bias and sensitivity analyses were conducted by Comprehensive Meta-Analysis, version 2.0 software. Results: Seventy-eight studies were retrieved from the databases, with nine studies included in the final analysis. Based on five genetic models, there was no association between ApaI (rs7975232), TaqI (rs731236), BsmI (rs1544410), FokI (rs2228570), and BglI (rs739837) polymorphisms and susceptibility to dental caries, except for the FokI (rs10735810) polymorphism. Conclusion: Among the VDR polymorphisms considered, an association was found between the FokI (rs10735810) polymorphism and the risk of dental caries, with a protective role of the f allele and ff genotype.